The Paragraph: The Core Of Text Writing - Aparicio, Marco; Ruíz, Lillian (CIEX JOURNAL, 2017)
The “paragraph” is the main component of the academic writing process. So, the construction of it is essential for effective communication in the academic and scientific fields. In this workshop, the participants will be guided, firstly, to reading the comprehension of a text and then to the construction of paragraphs from the identification of their characteristics and main elements, obtaining as products the development of a graphic organizer and a coherent paragraph. It has been observed that both students and professionals in the area of language teaching have some difficulties both in comprehension and in the writing of academic texts. This may be due to a number of reasons, such as the lack of continuous practice in academic reading and writing, lack of proper use of grammatical elements and proper spelling in the language, inadequate guidance of the learning process during school life, lack of adequate organization of both the ideas we are reading and those we produce in the written text, among others. The purpose of this workshop is to help strengthen this area by sharing with the participants some techniques for the proper carry out reading comprehension and the effective integration of paragraphs that in a coherent way express our ideas, having as products of this workshop graphic organizers for reading, as well as the writing of paragraphs that meet the basic characteristics of cohesion and coherence. The work strategy will be based (1) on team learning, recovering the experiences of its members, and (2) through the intervention of facilitators in presenting some concepts.